PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIIA SMP NEGERI 1 SINDUE TOMBUSABORA - Dian Oktaviani; Anggraini Anggraini; Nurhayadi Nurhayadi; Muhammad Fachri B. Paloloang (Universitas Tadulako, 2025)
This study aims to describe the implementation of the Search, Solve, Create, and Share (SSCS) learning model in improving the mathematical problem-solving abilities of seventh-grade students at SMP Negeri 1 Sindue Tombusabora. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart design, which consists of four stages: planning, action, observation, and reflection. The research subjects were 20 students of class VII A, with three students selected as informants. The research was conducted in two cycles. Based on the final action test results, the percentage of classical learning mastery increased from 60% in the first cycle to 88.23% in the second cycle. Teacher and student observations also improved from a good category in the first cycle to a very good category in the second. The SSCS model was implemented through several phases: (1) introduction, where prior knowledge was explored through discussion; (2) search, where contextual problems related to real-life situations were introduced; (3) solve, where students analyzed information to identify patterns and draw preliminary conclusions; (4) create, where students formulated solutions in the form of simple posters; (5) share, where students presented their results in front of the class; and (6) conclusion, where students and the teacher reflected together. The findings indicate that the SSCS model effectively enhances students' mathematical problem-solving skills.